Knowledge and Perception Regarding Medication Error Among Nurses - Maharjan, Susan; Shrestha, Amrita; Shakya, Vivechana; Maharjan, Manju; Panthee, Bimala; Joshi, Rashmi (Journal of Nepal Health Research Council, 2024)
Background: Patient safety is the major concern in providing quality care. Medication errors have been identified as the most common type of preventable errors. This study aimed to assess the knowledge and perception regarding medication error among nurses. Methods: A quantitative cross-sectional research design was used. The study was conducted in four different private hospitals in Lalitpur. A total enumerative sampling technique was used to select 302 nurses from these hospitals. Descriptive statistical methods were used to assess socio-demographic variables and inferential statistics methods such as the chi-squared test was used to analyse the association between knowledge, perception, and its socio-demographic characteristics. Results: Most of the respondents 244 (80.8%) agreed the cause of medication error occurs due to unclear handwriting and 217 (71.9%) agreed prescribing the wrong route or dose and time. Mostly respondents 126 (41.7%) had inadequate knowledge, 101 (33.4%) had adequate knowledge and 75 (24.8%) had moderate knowledge on medication error. Mostly respondents 273 (90.4%) had positive perception and 26 (8.6 %) had negative perception. Conclusions: Most of the nurses had inadequate knowledge but has positive perception on medication error. Appropriate strategies for reducing nurses’ workload, barriers to reporting, and sensitization workshops in a regular basis by the administrator should be developed to address medication errors and enhance patient safety in hospital settings. Keywords: Knowledge; medication error; nurses; perception.